2016
DOI: 10.15666/aeer/1403_479487
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Agricultural Chemicals on Selected Heavy Metals Accumulation in Herb Plants

Abstract: Abstract. The aim of this paper is to determine cadmium, lead and nickel concentration in different herb plants and in the soil collected in the areas close to winter wheat and grain maize fields. The following herbs were analyzed: Achillea millefolium, Cichorium intybus L., Equisetum arvense, Polygonum persicaria, Plantago lanceolata L., and Plantago major L.. They were sampled one and ten meters away from the edge of the fields. The plants, 70 of each species, were collected during the flowering stage from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…The average value for all species was the highest at 15 m from the road for Cd and at 1 m for Pb. The findings of the present experiment indicated that in the case of Pb the average coefficient value for all grass species, and distances from the road were much lower than that provided by Malinowska and Jankowski ( 2016 ).…”
Section: Resultscontrasting
confidence: 77%
“…The average value for all species was the highest at 15 m from the road for Cd and at 1 m for Pb. The findings of the present experiment indicated that in the case of Pb the average coefficient value for all grass species, and distances from the road were much lower than that provided by Malinowska and Jankowski ( 2016 ).…”
Section: Resultscontrasting
confidence: 77%
“…Thus, the accumulation coefficient of Ba and Li in herbs was estimated as average, while for Ti it was low [16]. The coefficient values for plants indicated varied accumulation of metals from the soil, which was also demonstrated in many other studies [19,[30][31][32][33][34]. The highest Ba, Li and Ti accumulation coefficient was recorded in Mentha arvensis L., in addition to Ba in Potentilla anserina L. (Table 6) and Li in Achillea millefolium L. (Table 7).…”
Section: Resultsmentioning
confidence: 77%